(untitled) (Experimental biology, 2025)
Genome editing using CRISPR-Cas9 has become a powerful tool in modern biotechnology to precisely modify the genomic sequences of various organisms. In plant biology, CRISPR-Cas9 technology is of particular importance because it allows efficient modification of plant genomes to improve crops and develop new varieties with desirable traits. This study aims to develop a CRISPR/Cas genetic system based on a viral vector for plant genome editing. The introduction of CRISPR-Cas9 genomic editing in plants based on viral vectors offers significant potential for crop improvement and addressing disease resistance, climate change, and nutritional traits. To obtain transient expression of Cas9 in plants, we used plasmids pKSE401 that contain nuclease containing spCas9 with an optimized maize codon under the control of the 35S promoter for expression in plant tissue. The design of guide RNAs for the PDS gene was carried out in CRISPR-P-2.0 and CRISPOR programs. Sol Genomics Network (SGN) database was used to obtain reference genes and sequence validation was performed by Blast-Nucleotide alignment. Guide RNAs were "sewn" into the plasmid by GoldenGate cloning. The expression of Cas9 in the viral vector in Nicotiana benthamiana L. plants was analyzed. The results of the work based on the use of the CRISPR-Cas9 system and viral vectors for plant genome editing are highly competitive in comparison with known analogs in Kazakhstan and the world. This approach provides accuracy, efficiency, and flexibility of making changes in plant genomes, surpassing traditional breeding methods and other genome editing technologies.